PERLINDUNGAN KONSUMEN PARFUM ISI ULANG YANG TIDAK TERDAFTAR DI BADAN PENGAWAS OBAT DAN MAKANAN - Zayyan, Khalillah; Anggraini, Anna Maria Tri (Tribuere, 2023)
Refill perfume is the type of perfume that is in great demand by Indonesian people as the market price is much cheaper. With high interest, this condition can be abused by business actors by producing the perfume without looking back at the regulations. Based on Drug and Food Supervisory Body (BPOM) data, the number of perfume refills in DKI Jakarta was found to be 64.6% containing too much methanol, which in judgement decision number 1325/Pid.Sus/2018/Pn.JktBrt. The problem that the authors discuss in this study is how are the regulations regarding supervision of refill perfume? and what is the form of legal protection for refill perfume consumers who are not registered with Drug and Food Supervisory Body (BPOM) in the judgement number 1325/Pid.Sus/2018/Pn.Jkt.Brt based on Law No. 8 of 1999 concerning Consumer Protection? This study uses research methods with the type of normative legal research with the nature of the research that is descriptive and qualitatively analyzed, drawing conclusions based on a deductive mindset. The results of the analysis show that regarding the legal protection given to refill perfume consumers in the judgement number 1325/Pid.Sus/2018/Pn.Jkt Brt in the form of preventive and repressive legal protection which has been regulated in Law Number 8 of 1999 concerning Consumer Protection and Drug and Food Supervisory Body regulations. As for the regulations governing the supervision of refill perfume, this is based on BPOM Regulations.